Preparation method and application of nNi / Rh (x)-La2O3 catalyst

By preparing nNi/Rh(x)-La2O3 catalyst, the problem of low catalyst catalytic efficiency in the prior art is solved, and efficient photocatalytic degradation of methyl acrylate is achieved, thereby reducing environmental pollution.

CN119857498AActive Publication Date: 2025-04-22WEIFANG UNIVERSITY

Patent Information

Application Number
CN202510346046.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

In the prior art, the catalyst used for photocatalytic degradation of methyl acrylate has low catalytic efficiency and is difficult to effectively degrade the substance, resulting in environmental pollution.

Method used

A nNi/Rh(x)-La2O3 catalyst was prepared, and a catalyst with high catalytic activity was formed by preparing La2O3 support particles, supporting and activation treatment of Rh and Ni.

Benefits of technology

This catalyst exhibits excellent performance when photocatalyzed methyl acrylate, can effectively reduce the concentration of methyl acrylate, reduce environmental pollution, and significantly improve catalytic activity through the synergistic catalytic action of Ni and Rh.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857498A_ABST
    Figure CN119857498A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an nNi / Rh (x)-La2O3 catalyst, and belongs to the technical field of catalysts. According to the technical scheme, the preparation method comprises the following steps: 1) preparing La2O3 carrier particles: screening lanthanum nitrate, dropwise adding a nitric acid solution into the lanthanum nitrate, mixing, drying and calcining; 2) preparation of Rh (x)-La2O3: adding the La2O3 carrier particles and Rh (NO3) 3.2 H2O into water, and stirring for reaction; drying and calcining to obtain an Rh (x)-La2O3 carrier; and 3) preparation of the nNi / Rh (x)-La2O3 catalyst: dispersing the Rh (x)-La2O3 carrier in water, adding Ni (NO3) 2.6 H2O into the Rh (x)-La2O3 carrier, stirring, adjusting the pH value, carrying out a reaction, cleaning and drying the precipitate, and calcining to obtain the nNi / Rh (x)-La2O3 catalyst. The nNi / Rh (x)-La2O3 catalyst has very high catalytic activity, and has a good application prospect in photocatalytic degradation of methyl acrylate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a preparation method and application of a nNi / Rh(x)-La2O3 catalyst. Background Art

[0002] Methyl acrylate (MA) is a colorless, transparent liquid with a pungent odor and is easily soluble in organic solvents such as ethanol and ether. It is an important organic chemical raw material and is widely used in coatings, adhesives, plastics and other fields. However, methyl acrylate may produce pollutants such as wastewater and waste gas during its production and use. Photocatalytic degradation is a technology that uses photocatalysts to catalyze the decomposition of organic matter under light conditions. After absorbing light energy, photocatalysts can produce free radicals or electron-hole pairs with strong oxidizing properties. These free radicals or electron-hole pairs can react with organic matter and decompose it into harmless small molecules. Photocatalytic degradation technology has the advantages of high efficiency, environmental protection, and no secondary pollution. It has broad application prospects in wastewater treatment, air purification and other fields. Therefore, it is of great significance to study the photocatalytic degradation technology of methyl acrylate.

[0003] At present, certain research progress has been made in the photocatalytic degradation technology of methyl acrylate. The most widely used in the prior art is TiO2 photocatalytic degradation: TiO2 is a commonly used photocatalyst with excellent catalytic performance and stability. Studies have shown that under ultraviolet light, TiO2 can catalyze the degradation of methyl acrylate and decompose it into harmless substances such as CO2 and H2O. In addition, by modifying TiO2, such as doping with metal ions or compounding with other semiconductor materials, its photocatalytic performance can be further improved. In addition to TiO2, some other photocatalysts are also used for the degradation of methyl acrylate. For example, semiconductor materials such as ZnO and CdS. These photocatalysts can produce free radicals or electron-hole pairs under light conditions, thereby catalyzing the decomposition of methyl acrylate. However, the catalysts in the prior art often have the problem of low catalytic efficiency, and it is necessary to develop a new catalyst for the photocatalytic degradation of methyl acrylate. Summary of the invention

[0004] The invention provides a preparation method and application of a nNi / Rh(x)-La2O3 catalyst. The nNi / Rh(x)-La2O3 catalyst has high catalytic activity and good application prospect in photocatalytic degradation of methyl acrylate.

[0005] The technical solution of the present invention is: In a first aspect, a method for preparing a nNi / Rh(x)-La2O3 catalyst is disclosed, comprising the following steps: 1) Preparation of La2O3 carrier particles: sieving lanthanum nitrate particles to 100-600 μm, adding nitric acid solution to lanthanum nitrate, mixing, drying and calcining to obtain La2O3 carrier particles, the particle size of the La2O3 carrier particles is 50-120 μm; 2) Preparation of Rh(x)-La2O3: Rh(NO3)3·2H2O is used as a precursor, and Rh is introduced into the surface of La2O3 by an impregnation method to prepare Rh(x)-La2O3; specifically, the La2O3 carrier particles prepared in step 1) and Rh(NO3)3·2H2O are added to water and stirred at 50-60°C for 5-8h; the resulting viscous substance is dried in an oven at 90-110°C for 10-16h to obtain a solid powder, and then the solid powder is transferred to a tube furnace and calcined in a helium atmosphere at 850-950°C for 4-8h to obtain a Rh(x)-La2O3 carrier, wherein x=2, 4, 6, 8, 10, and x represents the mass percentage of Rh in the carrier; 3) Preparation of nNi / Rh(x)-La2O3 catalyst: Ni is loaded onto the Rh(x)-La2O3 carrier by the deposition precipitation method. The Rh(x)-La2O3 carrier is first activated and then dispersed in water. Ni(NO3)2·6H2O is added thereto and stirred for 40-60 min. The pH is adjusted to 9-12 and reacted at 80-100°C for 10-12 h. The precipitate is washed and dried. The catalyst is calcined in a tubular furnace under argon or helium conditions at a temperature of 300-400°C for 3-5 h. The temperature is then raised to 650-750°C for a second calcination for 3-4 h. The resulting sample is the nNi / Rh(x)-La2O3 catalyst, where n=1, 5, 10, and n is the mass percentage of Ni in the carrier.

[0006] Preferably, in step 1), the drying temperature is 80-100° C., the drying time is 4-8 h, the calcination temperature is 500-600° C., and the calcination time is 5-8 h.

[0007] Preferably, the concentration of the nitric acid solution in step 1) is 0.08-0.12 mol / L, and the mass volume ratio of lanthanum nitrate and nitric acid solution in step 1) is (20-50) g:1 mL.

[0008] Preferably, in step 2), the mass volume ratio of La2O3 carrier particles, Rh(NO3)3·2H2O and water is 100 g: (6-65) g: (300-400) mL.

[0009] Preferably, in step 3), the mass volume ratio of Rh(x)-La2O3 carrier, Ni(NO3)2·6H2O and water is 100 g: (4-50) g: (300-400) mL.

[0010] Preferably, the concentration of dilute nitric acid used for activation in step 3) is 0.08-0.12 mol / L. The specific activation method is: place the Rh(x)-La2O3 carrier in a reaction vessel, add dilute nitric acid solution, adjust the pH to 2-4, stir at 80-120°C for 8-12h, and then dry at 100-150°C for 10-24h, and finally calcine at 300-400°C for 4-5h.

[0011] Preferably, in step 3), Na2CO3 or ammonia water is used to adjust the pH.

[0012] Preferably, in step 3), the drying is performed at 80-100° C. for 10-12 hours.

[0013] In a second aspect, the use of the catalyst in photocatalytic degradation of methyl acrylate is disclosed, comprising the following steps: A. Place the nNi / Rh(x)-La2O3 catalyst in a photoreactor, the set temperature of the photoreactor is 20-30°C and the pressure is 0.1-0.3MPa; B. Add methyl acrylate solution to the photoreactor and stir for 90-110 min in dark conditions; C. Under the irradiation of a xenon lamp with an irradiation power of 350W, start the condensing device, maintain 0°C, and carry out the degradation reaction for 5-7 hours. Use a gas chromatography-mass spectrometer to detect the mixed solution after the reaction.

[0014] Nickel and rhodium are loaded on the surface of La2O3 carrier to form Rh2O3 and NiO metal oxide layers, which improve the catalytic performance of the catalyst. Rh optimizes the strong interaction between metal Ni and the carrier, thereby improving the catalytic performance. At the same time, the presence of Ni enhances the electron transfer between the La2O3 carrier and Rh, thereby promoting the degradation of methyl acrylate. The introduction of Rh on the surface of La2O3 to generate metal oxide Rh2O3 is the key to improving catalytic activity. The addition of Rh effectively inhibits the sintering of La2O3 during high-temperature calcination, significantly increases the specific surface area of ​​the catalyst, and provides more mesoporous structures, thereby optimizing the dispersion of Ni. There is an electron transfer phenomenon between La2O3 and the active component Ni, which makes Ni and the Rh(x)-La2O3 carrier have a strong interaction, which not only protects Ni from the high-temperature sintering phenomenon, but also optimizes the bond energy between Rh and methyl acrylate during the catalytic reaction, which is beneficial to the degradation of methyl acrylate, thereby significantly improving the catalytic activity.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The nNi / Rh(x)-La2O3 catalyst prepared by the present invention exhibits excellent performance in photocatalytic degradation of methyl acrylate, and can effectively reduce the concentration of methyl acrylate and reduce environmental pollution.

[0016] 2. The high specific surface area and suitable pore size distribution of La2O3 of the present invention are conducive to the uniform dispersion of Rh, thereby improving the catalytic activity. When Ni and Rh coexist in the catalyst, a synergistic catalytic effect can be produced. This synergistic effect can significantly improve the catalytic activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a morphology diagram of the catalyst prepared in Example 1 of the present invention.

[0018] Figure 2 1 is the degradation curve of methyl acrylate over time in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0019] In order to enable persons skilled in the art to better understand the technical solution in the present invention, the technical solution will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0020] Example 1 The preparation method of the nNi / Rh(x)-La2O3 catalyst comprises the following steps: 1) Preparation of La2O3 carrier particles: lanthanum nitrate particles were sieved to 100 μm, 1 mL of 0.08 mol / L nitric acid solution was added dropwise to 20 g of lanthanum nitrate, the mixture was dried at 80°C for 8 h, and then calcined at 600°C for 5 h to obtain La2O3 carrier particles with a particle size of 50 μm; 2) Preparation of Rh(x)-La2O3: 100 g of the La2O3 carrier particles prepared in step 1) and 6 g of Rh(NO3)3·2H2O were added to 300 mL of water and stirred at 50°C for 8 h; the resulting viscous material was dried in an oven at 90°C for 16 h to obtain a solid powder, which was then transferred to a tube furnace and calcined at 850°C in a helium atmosphere for 8 h to obtain a Rh(x)-La2O3 carrier, wherein x=2, and x represents the mass percentage of Rh in the carrier; 3) Preparation of nNi / Rh(x)-La2O3 catalyst: The Rh(x)-La2O3 carrier was first activated. The specific activation method was as follows: 100 g of the Rh(x)-La2O3 carrier was placed in a reaction vessel, 200 mL of deionized water was added, 0.08 mol / L of dilute nitric acid solution was added dropwise, the pH was adjusted to 2, and the catalyst was stirred at 80°C for 12 h, then dried at 100°C for 24 h, and finally calcined at 300°C for 5 h; 100 g of the activated Rh(x)-La2O3 The carrier was dispersed in 300 mL of water, 4 g of Ni(NO3)2·6H2O was added thereto, stirred for 40 min, the pH was adjusted to 9 with ammonia water, reacted at 80°C for 12 h, the precipitate was washed, and dried at 80°C for 12 h; calcined in a tubular furnace under argon conditions at 300°C for 5 h, then heated to 650°C for a second calcination for 4 h. The obtained sample was the nNi / Rh(x)-La2O3 catalyst, where n=1, n is the mass percentage of Ni in the carrier. The morphology of the prepared catalyst is shown in FIG. Figure 1 shown.

[0021] The use of the catalyst in the photocatalytic degradation of methyl acrylate comprises the following steps: A. Place 20 mg of nNi / Rh(x)-La2O3 catalyst in a photoreactor, the set temperature of the photoreactor is 20°C and the pressure is 0.1 MPa; B. Add 20 mg / L methyl acrylate solution to the photoreactor and stir for 90 min in dark conditions; C. Under the irradiation of a xenon lamp with an irradiation power of 350 W, start the condensing device, maintain 0°C, and carry out the degradation reaction for 6 hours. Use a gas chromatography-mass spectrometer to detect the mixed solution after the reaction.

[0022] Example 2 The preparation method of the nNi / Rh(x)-La2O3 catalyst comprises the following steps: 1) Preparation of La2O3 carrier particles: lanthanum nitrate particles were sieved to 300 μm, 1 mL of 0.1 mol / L nitric acid solution was added dropwise to 30 g of lanthanum nitrate, the mixture was dried at 90°C for 6 h, and then calcined at 550°C for 6 h to obtain La2O3 carrier particles with a particle size of 80 μm; 2) Preparation of Rh(x)-La2O3: 100 g of the La2O3 carrier particles prepared in step 1) and 30 g of Rh(NO3)3·2H2O were added to 350 mL of water and stirred at 55°C for 6 h; the resulting viscous material was dried in an oven at 100°C for 12 h to obtain a solid powder, which was then transferred to a tube furnace and calcined at 900°C in a helium atmosphere for 6 h to obtain a Rh(x)-La2O3 carrier, wherein x=6, and x represents the mass percentage of Rh in the carrier; 3) Preparation of nNi / Rh(x)-La2O3 catalyst: The Rh(x)-La2O3 carrier was first activated. The specific activation method was as follows: 100 g of the Rh(x)-La2O3 carrier was placed in a reaction vessel, 200 mL of deionized water was added, 0.1 mol / L of dilute nitric acid solution was added dropwise, the pH was adjusted to 3, and the mixture was stirred at 100 °C for 10 h, then dried at 120 °C for 16 h, and finally calcined at 350 °C for 4 h; 100 g of the activated Rh(x)-La2O3 carrier was placed in a reaction vessel, 200 mL of deionized water was added, 0.1 mol / L of dilute nitric acid solution was added dropwise, the pH was adjusted to 3, and the mixture was stirred at 100 °C for 10 h, then dried at 120 °C for 16 h, and finally calcined at 350 °C for 4 h. The a2O3 carrier was dispersed in 350 mL of water, 26 g of Ni(NO3)2·6H2O was added thereto, stirred for 50 min, the pH was adjusted to 10 with sodium carbonate, reacted at 90°C for 11 h, the precipitate was washed, and dried at 90°C for 11 h; calcined in a tubular furnace under argon conditions at 350°C for 4 h, then heated to 700°C for a second calcination for 3.5 h. The obtained sample was the nNi / Rh(x)-La2O3 catalyst, where n=5, and n is the mass percentage of Ni in the carrier.

[0023] The use of the catalyst in the photocatalytic degradation of methyl acrylate comprises the following steps: A. 20 mg of nNi / Rh(x)-La2O3 catalyst was placed in a photoreactor, and the set temperature of the photoreactor was 25°C and the pressure was 0.2 MPa; B. Add 20 mg / L methyl acrylate solution to the photoreactor and stir for 100 min in the dark; C. Under the irradiation of a xenon lamp with an irradiation power of 350 W, start the condensing device, maintain 0°C, and carry out the degradation reaction for 5 hours. Use a gas chromatography-mass spectrometer to detect the mixed solution after the reaction.

[0024] Example 3 The preparation method of the nNi / Rh(x)-La2O3 catalyst comprises the following steps: 1) Preparation of La2O3 carrier particles: lanthanum nitrate particles were sieved to 600 μm, 1 mL of 0.12 mol / L nitric acid solution was added dropwise to 50 g of lanthanum nitrate, the mixture was dried at 100°C for 4 h, and then calcined at 500°C for 8 h to obtain La2O3 carrier particles with a particle size of 120 μm; 2) Preparation of Rh(x)-La2O3: 100 g of the La2O3 carrier particles prepared in step 1) and 65 g of Rh(NO3)3·2H2O were added to 400 mL of water and stirred at 60°C for 5 h; the resulting viscous material was dried in an oven at 110°C for 10 h to obtain a solid powder, which was then transferred to a tube furnace and calcined at 950°C in a helium atmosphere for 4 h to obtain a Rh(x)-La2O3 carrier, wherein x=10, and x represents the mass percentage of Rh in the carrier; 3) Preparation of nNi / Rh(x)-La2O3 catalyst: The Rh(x)-La2O3 carrier was first activated. The specific activation method was as follows: 100 g of the Rh(x)-La2O3 carrier was placed in a reaction vessel, 200 mL of deionized water was added, and 0.12 mol / L of dilute nitric acid solution was added. After adjusting the pH to 4, the catalyst was stirred at 120°C for 8 h, and then dried at 150°C for 10 h. Finally, the catalyst was calcined at 400°C for 4 h. 100 g of the activated Rh(x)-La2O3 carrier was placed in a reaction vessel, and 200 mL of deionized water was added. The 0.12 mol / L dilute nitric acid solution was added. After the pH was adjusted to 4, the catalyst was stirred at 120°C for 8 h, and then dried at 150°C for 10 h. Finally, the catalyst was calcined at 400°C for 4 h. The a2O3 carrier is dispersed in 400 mL of water, 50 g of Ni(NO3)2·6H2O is added thereto, stirred for 60 min, the pH is adjusted to 12 with aqueous ammonia, reacted at 100°C for 10 h, the precipitate is washed, and dried at 100°C for 10 h; calcined in a tubular furnace under argon gas at 400°C for 3 h, then heated to 750°C for a second calcination for 3 h, and the obtained sample is the nNi / Rh(x)-La2O3 catalyst, where n=10, and n is the mass percentage of Ni in the carrier.

[0025] The use of the catalyst in the photocatalytic degradation of methyl acrylate comprises the following steps: A. 20 mg of nNi / Rh(x)-La2O3 catalyst was placed in a photoreactor, and the set temperature of the photoreactor was 30°C and the pressure was 0.2 MPa; B. Add 20 mg / L methyl acrylate solution to the photoreactor and stir for 110 min in the dark; C. Under the irradiation of a xenon lamp with an irradiation power of 350W, start the condensing device, maintain 0°C, and carry out the degradation reaction for 7 hours. Use a gas chromatography-mass spectrometer to detect the mixed solution after the reaction.

[0026] Comparative Example 1 Different from Example 1, this comparative example does not include step 3) to prepare a Rh(x)-La2O3 carrier.

[0027] Comparative Example 2 The preparation method of the nNi / -La2O3 catalyst comprises the following steps: 1) Preparation of La2O3 carrier particles: lanthanum nitrate particles were sieved to 100 μm, 1 mL of 0.08 mol / L nitric acid solution was added dropwise to 20 g of lanthanum nitrate, the mixture was dried at 80°C for 8 h, and then calcined at 600°C for 5 h to obtain La2O3 carrier particles with a particle size of 50 μm; 2) Preparation of nNi / La2O3 catalyst: 100 g of La2O3 carrier was dispersed in 300 mL of water, 4 g of Ni(NO3)2·6H2O was added thereto, stirred for 40 min, the pH was adjusted to 9 with aqueous ammonia, reacted at 80°C for 12 h, the precipitate was washed, and dried at 80°C for 12 h; calcined in a tubular furnace under argon conditions at 300°C for 5 h, then heated to 650°C for a second calcination for 4 h. The obtained sample was the nNi / La2O3 catalyst, where n=1, and n is the mass percentage of Ni in the carrier.

[0028] Comparative Example 3 Different from Example 1, the lanthanum nitrate particles are not screened in step 1) of this comparative example, and the remaining preparation methods and steps are the same as those of Example 1.

[0029] Comparative Example 4 Different from Example 1, step 1) of this comparative example is: preparation of La2O3 carrier particles: sieve lanthanum nitrate particles to 100μm, add 1mL of 0.08mol / L nitric acid solution to 20g of lanthanum nitrate, mix and dry at 80℃ for 8h, then calcine at 650℃ for 8h to obtain La2O3 carrier particles with a particle size of 40μm; the rest of the preparation method and steps are the same as those in Example 1.

[0030] Comparative Example 5 The difference from Example 3 is that in this comparative example, step 2) is: Preparation of Rh(x)-La2O3: add 100g of La2O3 carrier particles prepared in step 1) and 80g of Rh(NO3)3·2H2O to 300mL of water, and stir at 50°C for 8h; dry the resulting viscous substance in an oven at 90°C for 16h to obtain a solid powder, and then transfer the solid powder to a tubular furnace and calcine it at 850°C in a helium atmosphere for 8h to obtain a Rh(x)-La2O3 carrier, wherein x=12, and x represents the mass percentage of Rh in the carrier; the rest of the preparation method and steps are the same as those in Example 3.

[0031] Comparative Example 6 Different from Example 1, in step 3), the Rh(x)-La2O3 carrier is not activated but directly dispersed in water. The rest of the preparation method and steps are the same as those in Example 1.

[0032] Comparative Example 7 The preparation method of the catalyst specifically comprises the following steps: 1) Preparation of La2O3 carrier particles: lanthanum nitrate particles were sieved to 100 μm, 1 mL of 0.08 mol / L nitric acid solution was added dropwise to 20 g of lanthanum nitrate, the mixture was dried at 80°C for 8 h, and then calcined at 600°C for 5 h to obtain La2O3 carrier particles with a particle size of 50 μm; 2) Preparation of nNi-La2O3 catalyst: 100 g of La2O3 carrier was dispersed in 300 mL of water, 4 g of Ni(NO3)2·6H2O was added thereto, stirred for 40 min, the pH was adjusted to 9 with aqueous ammonia, reacted at 80°C for 12 h, the precipitate was washed and dried; calcined in a tubular furnace under argon conditions at 300°C for 5 h, then heated to 650°C for a second calcination for 4 h. The obtained sample was the nNi-La2O3 catalyst, where n=1, and n is the mass percentage of Ni in the carrier.

[0033] 3) Preparation of Rh(x)-La2O3: The nNi-La2O3 catalyst prepared in step 2) was first activated. The specific activation method was as follows: 100 g of nNi-La2O3 carrier was placed in a reaction vessel, 200 mL of deionized water was added, 0.08 mol / L of dilute nitric acid solution was added dropwise, the pH was adjusted to 2, and then stirred at 80°C for 12 h, and then dried at 100°C for 24 h, and finally calcined at 300°C for 5 h; 100 g of activated nNi-La2O3 and 6 g of Rh(NO3)3·2H2O were added to 300 mL of water and stirred at 50°C for 8 h; the resulting viscous substance was dried in an oven at 90°C for 16 h to obtain a solid powder, and then the solid powder was transferred to a tubular furnace and calcined at 850°C in a helium atmosphere for 8 h to obtain a Rh(x)-La2O3 carrier, wherein x=2, and x represents the mass percentage of Rh in the carrier.

[0034] The catalysts prepared in the examples and comparative examples were tested for performance, and the test results are shown in Table 1.

[0035] Table 1 Catalyst performance test results

[0036] It can be seen from Table 1 that the catalyst prepared by the present invention has a larger average specific surface area and average pore size, and a larger crushing strength, which is more conducive to improving the catalytic performance.

[0037] The catalysts prepared in the above examples and comparative examples were used for photocatalytic degradation of methyl acrylate. The degradation methods in comparative examples 1-7 were the same as those in example 1. The test results are shown in Table 2. The degradation curves of methyl acrylate over time in example 1 and comparative example 1 are shown in Table 2. Figure 2 shown.

[0038]

[0039] η is the degradation rate of methyl acrylate, M 反应初 and M 反应后 are the concentration of methyl acrylate before and after the reaction, respectively.

[0040] Table 2 Photocatalytic degradation of methyl acrylate test results

[0041] As can be seen from Table 2, when the catalyst prepared by the present invention is applied to the decomposition of methyl acrylate, the decomposition conversion rate is high. In Comparative Example 1, Ni is not included, and the degradation rate of methyl acrylate is greatly reduced because Ni and Rh play a synergistic catalytic role in the nNi / Rh(x)-La2O3 catalyst system. When Ni is not included, the active center provided by Ni is lacking in the catalyst system, resulting in the adsorption and activation process of the reactant molecules being hindered, and the reaction is difficult to be carried out effectively, so the degradation rate of methyl acrylate is greatly reduced.

[0042] In Comparative Example 2, Rh is not included, and the degradation rate of methyl acrylate is greatly reduced. When Rh is not included, the number of active centers of the catalyst is reduced, resulting in difficulty in the efficient degradation reaction of methyl acrylate, and the degradation rate is significantly reduced.

[0043] In Comparative Example 3, the lanthanum nitrate particles are not screened, resulting in uneven particle size distribution. In the subsequent preparation of La2O3 carrier particles and loading of active components, the lanthanum nitrate particles with larger particle sizes may not fully react during calcination and other processes, resulting in the structure of the La2O3 carrier being not uniform and stable. At the same time, the uneven carrier particle size will affect the loading and dispersion of the active components (Ni and Rh), so that the active components cannot be evenly distributed on the carrier surface, thereby reducing the number of effective active sites.

[0044] In Comparative Example 4, the particle size of La2O3 is too small, which will change the stacking mode between the carrier particles, and the formed pore structure will be more fine and complex. Although a smaller particle size may increase the specific surface area, an excessively small pore size will cause the diffusion resistance of the reactant molecules to increase. In the reaction of photocatalytic degradation of methyl acrylate, it is difficult for the reactant molecules to quickly enter the pores of the catalyst and contact the active sites, which limits the reaction. At the same time, an excessively small particle size may also cause the mechanical strength of the carrier to decrease, and it is easy to agglomerate and break during the reaction, further affecting the stability and activity of the catalyst, so that the degradation rate of methyl acrylate is affected.

[0045] In Comparative Example 5, the amount of Rh loaded is too much, and Rh will agglomerate on the surface of the carrier to form larger particles. This will result in a decrease in the dispersion of Rh and a reduction in the number of effective active sites. Too much Rh may also block the pores of the carrier, reduce the average pore size and specific surface area of ​​the catalyst, and hinder the diffusion and adsorption of reactant molecules. In addition, excessive Rh may interact with Ni, change the electronic structure and surface properties of the catalyst, and have an adverse effect on the catalytic activity, thereby causing a decrease in the degradation rate of methyl acrylate.

[0046] In Comparative Example 6, the Rh(x)-La2O3 carrier is not activated and is directly dispersed in water. The purpose of the activation treatment of the carrier is to improve the surface properties of the carrier and increase its loading capacity and dispersion of the active component (Ni). The steps of acid treatment, stirring, drying and calcination in the activation process can remove impurities on the surface of the carrier, increase the active groups on the surface, make the surface of the carrier more uniform and conducive to the attachment of active components. When no activation treatment is performed, the properties of the carrier surface are not conducive to the loading and dispersion of Ni, and Ni may not be evenly distributed on the surface of the carrier, resulting in uneven number and distribution of active sites, which will hinder the contact between the reactant molecules and the active sites, thereby reducing the catalytic performance of the catalyst and reducing the degradation rate of methyl acrylate.

[0047] In Comparative Example 7, changing the loading order of Rh and Ni, loading Ni first and then loading Rh, will result in Rh being unable to be well loaded on the Ni-La2O3 surface, thereby reducing the degradation rate.

[0048] The catalyst prepared in Example 1 was subjected to a cyclic performance test. The specific catalytic method was the same as that in Example 1. After one catalytic reaction, the catalyst activity needed to be restored. Specifically, the catalyst after the catalytic reaction was first filtered and collected, washed with deionized water, dried at 100°C for 11 hours, and then placed in a tubular furnace for calcination for 8 hours at a heating temperature of 650°C. The degradation rate after 10 cycles is shown in Table 3.

[0049] Table 3 Degradation rate of cycle performance test

Claims

1. A method for preparing a nNi / Rh(x)-La2O3 catalyst, characterized in that: The following steps are involved: 1) Preparation of La2O3 carrier particles: sieving lanthanum nitrate particles to 100-600 μm, adding nitric acid solution to lanthanum nitrate, mixing, drying and calcining to obtain La2O3 carrier particles, the particle size of the La2O3 carrier particles is 50-120 μm; 2) Preparation of Rh(x)-La2O3: Add the La2O3 carrier particles prepared in step 1) and Rh(NO3)·2H2O into water and stir at 50-60°C for 5-8h; dry the resulting viscous material in an oven at 90-110°C for 10-16h to obtain a solid powder, then transfer the solid powder to a tube furnace and calcine it at 850-950°C in a helium atmosphere for 4-8h to obtain a Rh(x)-La2O3 carrier, wherein x=2, 4, 6, 8, 10, and x represents the mass percentage of Rh in the carrier; 3) Preparation of nNi / Rh(x)-La2O3 catalyst: The Rh(x)-La2O3 carrier is first activated and then dispersed in water, Ni(NO3)2·6H2O is added thereto, stirred for 40-60 min, the pH is adjusted to 9-12, and the reaction is carried out at 80-100°C for 10-12 h. The precipitate is washed and dried; calcined in a tubular furnace under argon or helium conditions at a temperature of 300-400°C for 3-5 h, and then the temperature is raised to 650-750°C for a second calcination for 3-4 h. The resulting sample is the nNi / Rh(x)-La2O3 catalyst, where n=1, 5, 10, and n is the mass percentage of Ni in the carrier.

2. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: In step 1), the drying temperature is 80-100°C, the drying time is 4-8h, the calcination temperature is 500-600°C, and the calcination time is 5-8h.

3. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: The concentration of the nitric acid solution in step 1) is 0.08-0.12 mol / L, and the mass volume ratio of lanthanum nitrate and nitric acid solution in step 1) is (20-50) g:1 mL.

4. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: In step 2), the mass volume ratio of La2O3 carrier particles, Rh(NO3)3·2H2O and water is 100 g: (6-65) g: (300-400) mL.

5. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: In step 3), the mass volume ratio of Rh(x)-La2O3 carrier, Ni(NO3)2·6H2O and water is 100 g: (4-50) g: (300-400) mL.

6. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: The concentration of dilute nitric acid used for activation in step 3) is 0.08-0.12 mol / L. The specific activation method is: place the Rh(x)-La2O3 carrier in a reaction vessel, add dilute nitric acid solution, adjust the pH to 2-4, stir at 80-120°C for 8-12h, and then dry at 100-150°C for 10-24h, and finally calcine at 300-400°C for 4-5h.

7. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: In step 3), Na2CO3 or ammonia water is used to adjust the pH.

8. The method for preparing the nNi / Rh(x)-La2O3 catalyst according to claim 1, characterized in that: In step 3), the drying is carried out at a temperature of 80-100° C. for 10-12 hours.

9. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 8 in photocatalytic degradation of methyl acrylate, characterized in that: The following steps are involved: A. Place the nNi / Rh(x)-La2O3 catalyst in a photoreactor, the set temperature of the photoreactor is 20-30°C and the pressure is 0.1-0.3MPa; B. Add methyl acrylate solution to the photoreactor and stir for 90-110 min in dark conditions; C. Under the irradiation of a xenon lamp with an irradiation power of 350W, start the condensing device, maintain 0°C, and carry out the degradation reaction for 5-7 hours. Use a gas chromatography-mass spectrometer to detect the mixed solution after the reaction.

Citation Information

Patent Citations

  • Nickel-supported mesoporous lanthanum oxide catalyst and preparation method thereof

    CN109731579A

  • Rh-Ni bimetallic catalyst and preparation method and application thereof

    CN119303593A

  • Oxidation-promoting catalyst and method for producing the same

    JP2020199469A

  • Nickel-based MOF film photocatalyst grown in-situ on foamed nickel surface, preparation method therefor, and application thereof

    US20230080563A1

Cited By

  • La2O3-ZnO-NiO / ZrO2 oxygen carrier as well as preparation method and application thereof

    CN120790161A

  • La2O3-ZnO-NiO / ZrO2 oxygen carrier, its preparation method and application

    CN120790161B